(untitled) (Journal of Kidney Cancer, 2023)
Although age younger than 46 years has been an independent criterion for genetic testing in hereditary renal cell carcinoma (hRCC), there is a lack of evidence in the literature. This study aims to analyze whether a 46-year-old cut-off should be considered an independent genetic testing criterion and to elucidate risk factors predicting a positive genetic test. Observational study from January 2010 to December 2021. All patients under 46 years with a non-metastatic kidney mass and surgical indication were included. We assume patients who relapse in the first 5 years of follow-up could have a positive genetic test. As risk factors for relapse, ergo positive genetic test, we consider those patients who presented multifocal, bilateral, or previous renal tumor. Of 2,232 nephrectomies for kidney cancer, 301 patients met the inclusion criteria. The median follow-up was 60 months (IQR 29-101). The estimated five-year RFS was 94.4% (95% CI 91.3-97.5). Tumor size, previous renal tumor, multifocality, bilaterality, and pT3 or pT4 stage were independent recurrence risk factors. Genetic testing was performed on 24 patients. 10 patients had pathogenic variants in the test, 8 of which recurred during their life. 46-year-old cut-off has shown low performance in genetic testing. Therefore, we recommend that it be considered only if other hRCC risk criteria exist. Multifocality, bilaterality, and previous renal tumor could predict a positive genetic test.